Thermal decomposition and recovery properties of ZnAl–CO3 layered double hydroxide for anionic dye adsorption: insight into the aggregative nucleation and growth mechanism of the LDH memory effect. Issue 20 (10th May 2017) - Santos, R. M. M.; Tronto, J.; Briois, V.; Santilli, C. V.
Abstract : The LDH memory effect is driven by an aggregative nucleation and growth mechanism limited by the adsorption of the anionic dye in on the external surface. Abstract : The thermal decomposition of carbonate-intercalated layered double hydroxide (ZnAl–CO3 -LDH) and recovery induced by water and dye solution addition were studied in situ by time-resolved wide angle X-ray scattering (WAXS) and time-resolved X-ray absorption spectroscopy (XAS), providing insights into the mechanisms of these structural transformations. LDH nanostructure recovery was driven by an aggregative nucleation and growth mechanism, which is limited by the steric hindrance caused by the adsorption of the Acid Blue 113 azo dye (AB) on the external surface of both the nanocrystalline tactoids and the exfoliated layers. The recovery behaviour in dye solution is consistent with the hypothesis of the LDH-recovery by a direct synthesis process, generating nanosized LDH particles with thickness about four times lower than those induced by water addition. These findings explain the higher AB adsorption capacity (1587 mg g −1 ) of calcined LDH, compared to pristine ZnAl–CO3 -LDH (261.8 mg g −1 ) and also the efficient recycling of the spent adsorbent.